As políticas de formação de professores e os desafios no fazer pedagógico na escola do campo do município de Placas (PA) - MILÉO, Irlanda do Socorro de Oliveira (Pontifícia Universidade Católica do Rio Grande do Sul, 2022)
The aim of the research was to identify how teachers position them selves in relation to teacher education policies and whether the training they have makes it possible to develop pedagogical practices that contemplate the reality of the schools in the field. This study occurred through a bibliographic review and a field research in a municipal school, located on highway BR 230 – Transa mazônica, km 200, rural area of Placas (PA), where the director, the pedagogical coordinator and three teachers of the said school answered a questionnaire, and the data generated were analyzed from a qualitative perspective. The research points out that due to the lack of offer of courses for teachers in the field that contemplate their different contexts, there is the emergence of numerous obs tacles for this professional to develop a good work, thus affecting not only the professional quality, but the learning of the students of the field. In addition, we believe it is necessary to make some reflections about teacher education policies in the Brazilian scenario, because although we realize that there is a manifestation of intentions regarding the initial and continued training of teachers today, it is necessary to consider, in a special way, those who work in the schools of the field, as a way of having an effectively inclusive education for these subjects.